Biosynthesis of Zinc Oxide Nanomaterials from Plant Extracts and Future Green Prospects: A Topical Review. (12th April 2021) - Huang, Yajing; Haw, Choon Yian; Zheng, Ziyue; Kang, Junyong; Zheng, Jin‐Cheng; Wang, Hui‐Qiong
Abstract: This paper conducts a survey of the synthesis of zinc oxide nanomaterials using bio‐ and green‐ approaches that have attracted researchers' attention. Compared to the traditional physical and chemical synthesis, the green method of biosynthesis stands out and has become a favorite route in the research field as it conforms to the sustainable development of modern society. The biosynthesis process of ZnO nanomaterials is mainly divided into two parts: one is the pretreatment of plant components; the other is the dissolving of plant extracts in zinc precursor solution to form ZnO nanomaterials. During this process, the precursor that provides the zinc source is reduced to precipitate zinc oxide. As a routine confirmatory test, a series of characterization techniques are conducted, and the results show that the synthesized zinc oxide nanomaterials can exhibit good antibacterial, photocatalytic, anti‐oxidant, and anti‐cancer properties. In addition, prominent trends and pivotal points in visualized networks of bioinspired zinc oxide are further verified and discussed in this work. An outlook for challenges and future studies is also provided. Abstract : This review highlights the recent research on biosynthesis of zinc oxide nanomaterials through the phytochemical compounds extracted in plants and summarizes the state‐of‐the‐art mechanistic formation of zinc oxide on a molecular level by methodical analysis of preceding studies.